Care of polder people in nursing homes – palliative care/end of life decision making - Scott, Lucy (2010)
ABSTRACT Background Dementia is a significant health and social care issue. There are currently 700,000 people with dementia in the United Kingdom and this number is expected to double in thirty years. Caring for a person with dementia can be extremely challenging due to the nature of the disease. Informal carers are fundamentally important for people with dementia, often allowing them to maintain their independence in the community. However carers are often old and frail themselves and need help and support to allow them to remain in their caring role. There are currently services and provisions available to support carers but these are not being utilised fully.